Intimate Partner Violence Screening and Counseling: An Introductory Session for Health Care Professionals - Madeleine W. Schrier; Steven C. Rougas; Ellen W. Schrier; Sadie Elisseou; Sarita Warrie (Association of American Medical Colleges, 2017)
Introduction Intimate partner violence is a serious public health concern in the United States. Despite recommendations that physicians should routinely screen their patients, research has shown that lack of specific training has resulted in many health care professionals feeling unable to adequately perform this difficult but vital task. Though many educational resources exist to teach intimate partner violence screening, they often lack specific guidance on how to navigate this difficult conversation. In addition, they often lack formal teaching on how to counsel and refer patients who are victims of intimate partner violence. Methods This unique module, intended for a small-group setting of four to eight students, contains an intimate partner violence checklist with sample language that covers both screening and counseling using a motivational interviewing framework. Additional materials include a checklist companion for tips on how to navigate the conversation, two cases for role-play, a facilitator guide, and an objective structured clinical encounter case and assessment rubric. Results This module was given to 260 second-year medical students at the Warren Alpert Medical School between 2015 and 2017 and was rated highly by almost 90% of students. Discussion After completing this module, learners will be able to appropriately screen for intimate partner violence as well as counsel and refer patients who have screened positive. By implementing this module, educators can increase the number of health care professionals able to broach this difficult conversation with patients who may be in need of help and may otherwise go unaided.